Answer:
D, E
Step-by-step explanation:
(4x - 1) ^2 = 11 => (take square roots of both sides)
4x - 1 = +\- sqrt(11) => (Add 1 to both sides)
4x - 1 + 1 = 1 +\-sqrt(11) =>
4x + 0 = 1 +\- sqrt(11) => (Divide both sides by 4)
x = ( 1 +\- sqrt(11) ) /4
Which are choices D and E
Answer:4
Step-by-step explanation:
It’s would be 4 because 47/15=3.23333 and because you said to the nearest hundred than it would be rounded to 4
<h2>Hello</h2>
The answers are:
a) The name of the function is y, and it's a Square Root Function.
b) Independent variable : x , dependent variable : y
c) The rule that assigns exactly one output to the very input is called "function".
d) 
<h2>Why?</h2>
The name of a function can be also given as a single letter (y). For this exercise, the name of the function is "y", and it's a Square Root Function.
The independent variable of a function is the variable we assign the different values. For this exercise, the independent variable is designated with the letter "x".
The dependent variable is the function itself (y), and it's called "dependent" variable because its values will always depend on the "independent variable".
A function is the rule that states that there is exactly one output (range value) to the very input (domain value). A function only exists when there is exactly one output value (range) for each given input (domain), if there is more than one output for each input, the function does not exist.
To evaluate a function we assign values to the independent variable(x), hence:

Have a nice day!
Answer:
A)

B)

C)

Step-by-step explanation:
We are given the function:

A)
Given that h(1) = 20, we want to find <em>k</em>.
h(1) = 20 means that <em>h</em>(x) = 20 when <em>x</em> = 1. Substitute:

Simplify:

Anything raised to zero (except for zero) is one. Therefore:

B)
Given that h(1) = 40, we want to find 2<em>k</em> + 1.
Likewise, this means that <em>h</em>(x) = 40 when <em>x</em> = 1. Substitute:

Simplify:

We can take the natural log of both sides:

By definition, ln(e) = 1. Hence:

Therefore:

C)
Given that h(1) = 10, we want to find <em>k</em> - 3.
Again, this meas that <em>h</em>(x) = 10 when <em>x</em> = 1. Substitute:

Simplfy:

Take the natural log of both sides:

Therefore:

Therefore:
